Designing of public vehicle driver's seat - Yahya, Mohd Shahir (2005)
The increasing number of accidents involving buses in Malaysia is a cause of concern for the general population that relies on commercial vehicles. Though there are many factors contributing to this, a seat design, which increases the comfort and alertness of the drivers, may help in reducing fatigue. Since commercial vehicles are imported, their fit with the Malaysian population have been not studied. Ergonomic design of driver's workstation is a necessary component not only for the safety of the population but more so for the driver's safety and health protection. A higher percentage of back and cervical pain has been reported among bus drivers than among workers in non-driving position. In designing a seat, there are many considerations that should be taken into account such as seat reference point, seat height, seat width, lumbar support, and the adjustability range of seat. The objective of tins study is to establish the appropriate parameters for designing a bus driver's seat for Malaysian bus drivers by considering their anthropometric dimensions. This study uses qualitative method such as observation and survey to collect the data. The relevant anthropometries data were used to propose the recommended seat design. The recommended and current seat designs were simulated to analyse the performance of the seat in context of the relative comfort experienced by the bus operators and comparisons were made. Simulation on the existing seat showed that it is not able to accommodate the Malaysian bus driver's population, especially in providing adequate support to operator's back (5th percentile male). The simulation was also used to determine the adjustable ranges of the workstation components so as to accommodate 90% of the male bus driver population.